Morphometric characterization of Indian mithuns - MUKHERJEE, SABYASACHI; MUKHERJEE, ANUPAMA; LONGKUMER, I; MECH, MOONMOON; KHATE, KOBU; P, PERUMAL; RAJKHOWA, C (The Indian Journal of Animal Sciences, 2014)
Mithun (Bos frontalis) is a rare domesticated bovine species available in North-Eastern Hills Region of our country. Morphometric data of 134 mithuns, viz. BW, SW, HW, BL, HG, FL, TL, NC, NL, EL, PS, HL and HC were analyzed. The physical coat colour was also analyzed. Nagaland and Mizoram mithuns are predominantly jet black. One of the most distinguishing features of mithun is white stocking of fore legs and hind legs irrespective of their sex. The present study will be helpful to generate mithun specific species descriptor to aid in genetic improvement and conservation programme of this unique animal.